2009
DOI: 10.1128/mcb.00764-09
|View full text |Cite
|
Sign up to set email alerts
|

The mTORC2 Complex Regulates Terminal Differentiation of C2C12 Myoblasts

Abstract: Rapamycin, a selective inhibitor of mTORC1 signaling, blocks terminal myoblast differentiation. We found that downregulation of rictor, a component of the mTORC2 complex, but not downregulation of raptor, a component of the mTORC1 complex, prevented terminal differentiation (fusion) of C2C12 myoblasts. Both rapamycin and rictor downregulation suppressed the phosphorylation of AKT(S 473 ), and rapamycin treatment of C2C12 myoblasts disrupted the mTORC2 complex. Importantly, downregulation of rictor inhibited TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 37 publications
4
81
1
Order By: Relevance
“…In both cases, results are shown from a single experiment but similar data were obtained in at least 3 independent experiments. results were seen with extracts from cells allowed to differentiate in the presence of RAD001 (lanes [8][9][10][11][12][13]. Figure 2A shows that lambda phosphatase was able to dephosphorylate 4E-BP1 in extracts prepared at 48 hours ( Fig.…”
Section: Rad001 Inhibits P70s6k But Maintains the Phosphorylation Of mentioning
confidence: 70%
See 3 more Smart Citations
“…In both cases, results are shown from a single experiment but similar data were obtained in at least 3 independent experiments. results were seen with extracts from cells allowed to differentiate in the presence of RAD001 (lanes [8][9][10][11][12][13]. Figure 2A shows that lambda phosphatase was able to dephosphorylate 4E-BP1 in extracts prepared at 48 hours ( Fig.…”
Section: Rad001 Inhibits P70s6k But Maintains the Phosphorylation Of mentioning
confidence: 70%
“…We and others have previously shown that rapamycin 10,12 or RAD001 26 potently inhibits myogenic differentiation in the C2C12 myoblast model system. Furthermore, we showed that although inhibition of mTORC1 reduced p70S6K activity, prevented the phosphorylation of rpS6, reduced protein synthesis rates and delayed myotube formation, paradoxically 4E-BP1 remained in a hyperphosphorylated form.…”
Section: Rad001 Inhibits P70s6k But Maintains the Phosphorylation Of mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we concluded that macrophage-derived AREG promote T reg function through activation of mTORC1 signaling in T regs . However, although rapamycin is thought to inhibit mTORC1 signaling preferentially, evidence indicates that rapamcyin also blocks mTORC2 signaling [58,59]. mTORC2 regulates cellular metabolism and the cytoskeleton, and recent studies suggest its role in modulation of T reg generation and function as well.…”
Section: Discussionmentioning
confidence: 99%